New horizons from Big Data and Artificial Intelligence : Challenges and opportunities for Management and Business - Dos-Santos, M.J.P.L. ("International Conference on Business & Technological Trends", 2020)
The present Technological Revolution —presents various challenges and opportunities: the rapid development of science and technology (Artificial Intelligence and Big Data), population growth, the increasing scarcity of water resources, desertification, and excessive consumption of a variety of non-renewable energy resources, and the present dissemination and application of disruptive technologies Represents the biggest challenges to deal with in the future in order to promote the sustainable development and achieve the Sustainable Development Goals (SDGs)